Internet Economic Toolkit for African Policy Makers - Kenny, Charles (World Bank, Washington, DC, 2012)
This toolkit presents a model of the likely impacts of the Internet on African telecommunications companies and Internet Service Provider revenues, models of the cost structure and potential reach of Internet service, data on the extent of Internet development in Africa, and examples of its current use. With this background, the toolkit goes on to discuss policy choices faced by countries that hope to expand Internet use within the context of needed telecommunications reform and government-private partnerships involving universities and NGOs.